Aktuelle Aspekte der Cholesteatomchirurgie – Teil 2: chirurgische Therapie im Wandel der Zeit - Schulze, Anja; Zahnert, Thomas (Laryngo-Rhino-Otologie, 2020)
Due to cholesteatoma's slowly progressive and destructive growth there is a risk of intracranial and potentially life-threatening complications. That's why every cholesteatoma is a basically absolute indication for surgery. Only asymptomatic and small retractions, so-called prae-cholesteatomas, may be under observation. While the first part of this article focused on the basics of pathogenesis and diagnostics, this one provides an overview of current surgical strategies, both proven and new ones.
Keywords: Cholesteatom; Gehörgangscholesteatom; Chirurgie; Kinder; Endoskopie; Rekonstruktion; Rezidivcholesteatom; Residualcholesteatom